Model of conflict management - Maulad Bahrol, Khadijah; Md Yusoff, Rosman; Md Amin, Noor Dina; Abdul Hamid, Mariam; Ismail, Fadillah (Penerbit Uthm, 2019)
The origin of contention idea is proportional to the historical backdrop of mankind. The event of contentions in each condition in which human is available appears to us as ordinary. The subject of the contention, particularly beginning from 1970's has been the focal point of fascination of authoritative life especially in the USA and the world. Indeed, one of the outcomes that makes individuals pitiful and the other one that causes workforce misfortunes and time loss of the associations has prompted nations to set up associations and has driven the associations to go to effectively to preparing so as to limit these issues (Dağlı & Sığrı, 2014).